Promoting Friendships in the Playground : a Peer Befriending Programme for Primary Schools. - Bishop, B. (Lucky Duck Books., 2006)
This book aims to assist teachers to train pupils aged 6 - 11 in peer befriending. The contents include comprehensive facilitator notes on running training programme for young people including Circle Time activities, pro-social games and necessary photocopiable worksheets. The contents are based on the author's own experiences of running such a programme to assist pro-social behaviour at breaks and lunchtimes. Also included in the book are some awareness raising sessions for support staff and lunchtime supervisors.